Developing a Strategic Model for the Pesantren Entrepreneurial Ecosystem: Integrating SWOT and Analytic Network Process (ANP) - Dzikrulloh; Firman Setiawan Setiawan; Tri Pujiati; Faizal Amir; Elfira Maya Adiba (LAN TABUR: Jurnal Ekonomi Syariah The Islamic University of KH. Achmad Muzakki Syah Jember, East Java. Jember Jln. Manggar Gebang Poreng 139A Patrang Jember Jawa Timur, 2026)
Introduction: Pesantren play a strategic role in shaping community life, particularly in promoting entrepreneurship and economic empowerment. However, the development of entrepreneurship within pesantren remains limited due to the absence of a well-established entrepreneurial ecosystem. Therefore, this study aims to identify strategic priorities for strengthening the entrepreneurial ecosystem in pesantren. Methods: This study employs a qualitative approach supported by quantitative analysis through the integration of SWOT (Strengths, Weaknesses, Opportunities, and Threats) and the Analytic Network Process (ANP). SWOT analysis is used to identify internal and external factors influencing the entrepreneurial environment of pesantren, while ANP evaluates the interrelationships among criteria to determine strategic priorities. Data were collected through in-depth interviews, questionnaires, and literature review. Results: The findings from the SWOT analysis show that pesantren are positioned in Cell V and Quadrant I, indicating strong internal capabilities and favorable external opportunities for developing a Shariah-based entrepreneurial ecosystem. The ANP analysis identifies four main priority strategies: strengthening capacity building, fostering organizational culture and governance, enhancing institutional cohesion, and developing human resources. Conclusion and suggestion: The study contributes by proposing a strategic model that can serve as a practical guideline for pesantren in developing their entrepreneurial ecosystem. The implementation of these integrated strategies is expected to promote sustainable entrepreneurship and strengthen economic independence within pesantren.